The Role of Self-regulated Learning in Coping with Postgraduate Students Academic Procrastination During the COVID-19 Pandemic in Malaysia - Trisnawati, Sri; Rahimi, Nik Mohd (Muslim Education Review, 2022)
Academic procrastination is generally associated with insufficient self-regulated learning. However, through a qualitative cased study, this research looks at another perspective which explores the academic procrastination experienced and the role of self-regulated learning strategies in motivational and behavioral aspects as coping mechanisms during the COVID-19 pandemic. Six research participants, postgraduate students at the National University of Malaysia, were selected through purposive sampling and follow-up interviews. This research discovered that postgraduate students demonstrate academic procrastination behaviors such as delaying starting and completing the task, deferring doing the assignment, having a time gap between planning and actual work, being more easily distracted, yet, having the self-assurance of being able to complete the assignment in time, and exhibiting a perfectionist personality trait. At the same time, academic procrastination was dominantly caused by the ambience of online learning during the COVID-19 pandemic and lack of social support. This study also discovered that the postgraduate students applied self-regulated learning motivational strategies such as mastery of self-talk, the relevant reinforcement strategy, the self-consequential strategy and the environment-forming strategy in rebuilding and maintaining motivation. Meanwhile, an effort regulation strategy and pursuing social support are carried out in the behavioral aspect of self-regulated learning strategies to reduce indulgence on academic procrastination. Concisely, self-regulated learning strategies have played a significant role in coping with academic procrastination during online learning throughout the COVID-19 pandemic.